2009
DOI: 10.1158/1078-0432.ccr-09-1262
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Inhibition of Cathepsin S Blocks Colorectal Tumor Invasion and Angiogenesis

Abstract: Purpose: Cathepsin S is a cysteine protease that promotes the invasion of tumor and endothelial cells during cancer progression. Here we investigated the potential to target cathepsin S using an antagonistic antibody, Fsn0503, to block these tumorigenic effects. Experimental Design: A panel of monoclonal antibodies was raised to human cathepsin S. The effects of a selected antibody were subsequently determined using invasion and proteolysis assays. Endothelial cell tube formation and aorta sprouting assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 46 publications
8
97
2
Order By: Relevance
“…81 Our group and others have identified critical roles for cathepsins in tumor growth, angiogenesis, invasion and metastasis using both genetic and pharmacological strategies in mouse models of cancer. [82][83][84][85][86][87] For example, during sequential stages of tumor development in the RIP1-Tag2 (RT2) model of pancreatic islet carcinogenesis, 88 we found that expression of a subset of cathepsins (B, C, H, L, S, X/Z) progressively increased. 82 Moreover, most of these cathepsins, except cathepsin L, were provided predominantly by infiltrating TAMs in different tumor microenvironments.…”
Section: Il-4 Induces Cysteine Cathepsin Activity In Tamsmentioning
confidence: 83%
“…81 Our group and others have identified critical roles for cathepsins in tumor growth, angiogenesis, invasion and metastasis using both genetic and pharmacological strategies in mouse models of cancer. [82][83][84][85][86][87] For example, during sequential stages of tumor development in the RIP1-Tag2 (RT2) model of pancreatic islet carcinogenesis, 88 we found that expression of a subset of cathepsins (B, C, H, L, S, X/Z) progressively increased. 82 Moreover, most of these cathepsins, except cathepsin L, were provided predominantly by infiltrating TAMs in different tumor microenvironments.…”
Section: Il-4 Induces Cysteine Cathepsin Activity In Tamsmentioning
confidence: 83%
“…These indicated that Cat S plays an important role in aspects of angiogenesis both in vitro and in vivo 3 . Furthermore, high Cat S expression has also been observed in a range of tumors such as prostate, astrocytomas, hepatocellular and pancreatic carcinomas [4][5][6][7] . The expression of Cat S together with Cat B was found in neoplastic prostatic cells from pre-invasive to invasive and clinically detectable stage 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Impaired angiogenesis and tumor growth were found in Cat Sdeficient mice, whereas opposite phenotypes shown in mice lacking of the endogenous inhibitor cystatin C 12 . The invasive and pro-angiogenic effects in preclinical and clinical evaluation were blocked by antibody Fsn0503 against Cat S 6 . The invasive behavior in U251MG glioblastoma cells was disrupted by a peptidic, irreversible Cat S inhibitor, 4-morpholineureaLeu-HomoPhe-vinylsulphone 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a panel of monoclonal antibodies was raised to human Cathepsin S [9]. The effects of a selected antibody were successfully determined by cellbased invasion and proteolysis assays.…”
Section: Antibody-mediated Inhibition Of Cathepsin S Blocks Tumor Invmentioning
confidence: 99%